HUBUNGAN ANTARA KEMATANGAN EMOSI DAN PENYESUAIAN DIRI PADA PEMBELAJARAN TATAP MUKA SISWA KELAS X DI MAN 3 TULUNGAGUNG - Laurina Eka Putri (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2023)
The purpose of this study was to determine whether there is a relationship between emotional maturity and self-adjustment in face-to-face learning in grade 10 students of MAN 3 Tulungagung. This study uses correlational quantitative methods with simple random sampling method which was conducted on a student population of 159 students with a sample of 48 students. The data collection technique used a scale of emotional maturity and self-adjustment scale. In data analysis, researchers used the normality test method, linearity test, and product moment correlation test with the SPSS 20.0 for the Windows program. The results of this study indicate that there is a relationship between emotional maturity and self-adjustment in face-to-face learning in grade 10 students of MAN 3 Tulungagung. This relationship is shown by the significant result of 0.000 with p <0.05 which states that the two variables are interrelated. An r-count of 0.744 means the correlation between emotional maturity and self-adjustment is classified as positive with a strong correlation. So, in this study, if the emotional maturity of the individual is high, then the adjustment is also high, as well as better.